2012
DOI: 10.1371/journal.pone.0032513
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Possesses Sap7 as a Pepstatin A-Insensitive Secreted Aspartic Protease

Abstract: Candida albicans exists in most people, but opportunistically causes severe diseases. One of the major virulence factors is secreted aspartic protease family, encoded by 10 SAP genes (1). Sap isozymes are suggested to contribute to many virulence processes. However, there is a controversy whether Sap family is really a major virulence factor or not, because use of pepstatin A showed little protective effect. In this study, we found Sap7 was a pepstatin A‐insensitive protease and tried to determine the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…For example, Plasmodium spp., the causative organisms of malaria, require proteases for full virulence [158]. C. albicans secretes ten types of aspartic proteases to degrade host tissues and evade immune cells [159,160]. Thus, designing an AMP that is activated by virulent proteases may confer high selectivity toward each pathogenic organism.…”
Section: Design Of Molecular-targeted Ampsmentioning
confidence: 99%
“…For example, Plasmodium spp., the causative organisms of malaria, require proteases for full virulence [158]. C. albicans secretes ten types of aspartic proteases to degrade host tissues and evade immune cells [159,160]. Thus, designing an AMP that is activated by virulent proteases may confer high selectivity toward each pathogenic organism.…”
Section: Design Of Molecular-targeted Ampsmentioning
confidence: 99%
“…We previously demonstrated (Staniszewska et al, 2014a) that compensatory up-regulation of SAP7 occurs in the Dsap mutant under serum influence. Moreover, according to (Aoki et al, 2012) pepstatin A did not have any effect on the Sap7 activity despite inhibiting other Saps suggesting a role of this protein in drug resistance. Therefore, in this study we additionally assayed the influence of Compound no.…”
Section: Discussionmentioning
confidence: 91%
“…Sap7 is the most divergent and least known member of the whole SAP gene family (Dos Santos, 2010). (Aoki et al, 2012) demonstrated that amino acid residues in close proximity to the enzyme's active site affect Sap7 insensitivity to pepstatin A. Among 9 amino acids identified, M242A and T467 prohibit pepstatin A to access to the active site of Sap7.…”
Section: Discussionmentioning
confidence: 99%
“…All types of Sap genes are suggested to contribute to various virulence processes, such as adhesion, invasion, degradation of host proteins, and macrophage escape. Therefore, it has been suggested that the virulence of C. albicans strains correlates with the level of proteolysis activity as well as with the number of Sap genes (3)(4)(5)(6).…”
mentioning
confidence: 99%